Detrimental Role of miRNA-144-3p in Intracerebral Hemorrhage Induced Secondary Brain Injury is Mediated by Formyl Peptide Receptor 2 Downregulation Both In Vivo and In Vitro. Issue 6 (June 2019) - Fan, Weijian; Li, Xiang; Zhang, Dongping; Li, Haiying; Shen, Haitao; Liu, Yizhi; Chen, Gang
Although microRNA-144-3p (miRNA-144-3p) has been shown to suppress tumor proliferation and invasion, its function in intracerebral hemorrhage (ICH)-induced secondary brain injury (SBI) remains unclear. Thus, this study was designed to investigate the role of miRNA-144-3p in ICH. To accomplish this, we used adult male Sprague-Dawley rats to establish an in vivo ICH model by injecting autologous blood, while cultured primary rat cortical neurons were exposed to oxyhemoglobin (OxyHb) to mimic ICH in vitro . To examine the role of miRNA-144-3p in ICH-induced SBI, we used an miRNA-144-3p mimic and inhibitor both in vivo and in vitro . Following ICH induction, we found miRNA-144-3p expression to increase. Additionally, we predicted the formyl peptide receptor 2 (FPR2) to be a potential miRNA-144-3p target, which we validated experimentally, with FPR2 expression downregulated when miRNA-144-3p was upregulated. Furthermore, elevated miRNA-144-3p levels aggravated brain edema and neurobehavioral disorders and induced neuronal apoptosis via the downregulation of FPR2 both in vivo and in vitro . We suspected that these beneficial effects provided by FPR2 were associated with the PI3K/AKT pathway. We validated this finding by overexpressing FPR2 while inhibiting PI3K/AKT in vitro and in vivo . In conclusion, miRNA-144-3p aggravated ICH-induced SBI by targeting and downregulating FPR2, thereby contributing to neurological dysfunction and neural apoptosis via PI3K/AKT pathway activation. These findings suggest that inhibiting miRNA-144-3p may offer an effective approach to attenuating brain damage incurred after ICH and a potential therapy to improve ICH-induced SBI.